Managing Islamic Education in a Pluralist Context: The Bali Bina Insani Pesantren Model of Social Harmony in Hindu-Majority Bali - Nurul Uswatun Khasanah; Ristianto, Fadjrie Mahardika; Habibi, M. Bagus; Mutiara, Azmi (JSP: Jurnal Studi Pesantren, 2025)
Bali, as Indonesia's most prominent Hindu-majority province, presents a distinctive context for examining the management of Islamic educational institutions within a pluralist and religiously diverse society. Despite constituting a minority community, Muslims in Bali maintain pesantren institutions that serve not only as centers of Islamic learning but as active contributors to the cultivation of interfaith tolerance and social harmony. This study examines the management model of Bali Bina Insani Pesantren in building social harmony within Bali's multicultural society, organized around three research objectives: analyzing the institutional conditions of Bali Bina Insani Pesantren, examining the role of pesantren management in fostering harmony among religious communities, and identifying the strategies employed by the pesantren in cultivating religiously tolerant attitudes among its students and the surrounding community. A qualitative approach was employed, with data collected through direct field observation, in-depth interviews, and documentation at the research site. The findings reveal that Bali Bina Insani Pesantren has developed a distinctive management model that integrates Islamic educational values with a principled commitment to interfaith respect and multicultural coexistence, positioning the pesantren as a constructive social institution within Bali's pluralist landscape. These findings contribute to the theoretical understanding of pesantren management in non-Muslim majority contexts and offer practical insights for Islamic educational institutions operating within religiously diverse societies.